Agronomic biofortification of cowpea with selenium: effects of selenate and selenite applications on selenium and phytate concentrations in seeds - Silva, Vinícius M [UNESP]; Boleta, Eduardo HM [UNESP]; Martins, Juliana T [UNESP]; dos Santos, Flavia LM [UNESP]; da Rocha Silva, Anne C [UNESP]; Alcock, Thomas D; Wilson, Lolita; de Sá, Marco E [UNESP]; Young, Scott D; Broadley, Martin R; White, Philip J; dos Reis, André R [UNESP] (Wiley, 2019)
BACKGROUND: Selenium (Se) is a nutrient for animals and humans, and is considered beneficial to higher plants. Selenium concentrations are low in most soils, which can result in a lack of Se in plants, and consequently in human diets. Phytic acid (PA) is the main storage form of phosphorus in seeds, and it is able to form insoluble complexes with essential minerals in the monogastric gut. This study aimed to establish optimal levels of Se application to cowpea, with the aim of increasing Se concentrations. The efficiency of agronomic biofortification was evaluated by the application of seven levels of Se (0, 2.5, 5, 10, 20, 40, and 60 g ha−1) from two sources (selenate and selenite) to the soil under field conditions in 2016 and 2017. RESULTS: Application of Se as selenate led to greater plant Se concentrations than application as selenite in both leaves and grains. Assuming human cowpea consumption of 54.2 g day−1, Se application of 20 g ha−1 in 2016 or 10 g ha−1 in 2017 as selenate would have provided a suitable daily intake of Se (between 20 and 55 μg day−1) for humans. Phytic acid showed no direct response to Se application. CONCLUSION: Selenate provides greater phytoavailability than selenite. The application of 10 g Se ha−1 of selenate to cowpea plants could provide sufficient seed Se to increase daily human intake by 13–14 μg d−1. © 2019 Society of Chemical Industry.
Keywords: crop production; fertilization; grain quality; plant nutrition; Vigna unguiculata